تأثير الري بمياه صرف أحواض تربية الأسماك على بعض الصفات المورفولوجية والإنتاجية والنوعية لمحصول الفول السوداني (سوري-1) - عبد العزيز محمد; هيفا سوسن; سعد أديب; عثمان علي (Latakia University Journal -Biological Sciences Series, 2019)
The research was carried out at the ASN research center of the General Authority for Fisheries in the Banias region in Tartous during two agricultural seasons 2017-2018 in order to study the effect of irrigation on wastewater of fish ponds on some morphological characteristics and some productive and qualitative characteristics of peanut yield (Syrian 1) Three treatments of water with three replicates per irrigation treatment: • Fresh water irrigation "witness". • Irrigation of mature fish ponds. • Irrigation of wastewater fish larva ponds .The results of the study showed the following: The irrigation of wastewater from the fish ponds has a positive effect on the morphological characteristics and improves the productive and qualitative characteristics. It was observed that the irrigation of the wastewater of the mature fish ponds exceeded both the wastewater treatment of the fish larva and the control. The research concluded to highlight the importance of using the drainage water of fish ponds to irrigate the peanut crop (Syrian - 1) for the richness of this water with dissolved solids. نفذ البحث في مركز بحوث السن التابع للهيئة العامة للثروة السمكية في منطقة بانياس في محافظة طرطوس خلال موسمين زراعيين 2017-2018م وذلك لدراسة تأثير الري بمياه صرف أحواض تربية الأسماك على بعض الصفات الفينولوجية وبعض المؤشرات الإنتاجية والنوعية لمحصول الفول السوداني (سوري-1) حيث تم استخدام ثلاث معاملات من المياه بثلاث مكررات لكل معاملة من معاملات الري وهي : الري بالمياه العذبة "شاهد". الري بمياه صرف أحواض تربية الأسماك الناضجة . الري بمياه صرف أحواض تربية الإصبعيات . وتبين من نتائج الدراسة مايلي : إن الري بمياه صرف أحواض تربية الأسماك يؤثر إيجابياً على الأطوار الفينولوجية ، ويحسن من المؤشرات الإنتاجية والنوعية ولوحظ أن الري بمياه صرف أحواض تربية الأسماك الناضجة تفوقت على معاملتي الري بمياه صرف الإصبعيات وعلى الشاهد ، كما تفوقت معاملة الري بمياه صرف أحواض تربية الإصبعيات على الشاهد . وخلص البحث إلى إبراز أهمية استخدام مياه صرف أحواض تربية الأسماك في ري محصول الفول السوداني صنف (سوري-1) لغنى هذه المياه بالمواد الصلبة المنحلة .